2018
DOI: 10.5812/jkums.69640
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Satureja hortensis L. Essential Oil on the Growth and Survival of Salmonella typhimorium in Minced Poultry Meat During Refrigerated Storage

Abstract: Background: Food products and in particular meat are regarded as one of the main sources of Salmonella genus bacteria; accordingly, researchers' attention has recently been drawn to the use of natural preservatives to increase shelf-life and eliminate foodrelated diseases. The present study was conducted to investigate the effect of Satureja hortensis L. (Summer savory plant) essential oil on the growth of Salmonella Typhimorium in poultry meat. Methods: In the present study, the effects of different concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Evaluating the savory extract effect on the shelf-life of fresh chicken meat at refrigeration temperature showed that meat oxidation and its microbial load significantly decreased [175]. In another study where Satureja hortensis L. EO was utilized to reduce the survival of S. typhimorium in minced poultry meat during refrigerated storage, it was reported that summer savory EO significantly decreased Salmonella count compared to the control group [176]. Applying Satureja montana L. EO as antioxidants in precooked pork chops during chilled storage showed to be effective in oxidation stability and warmed-over flavor formation [177].…”
Section: Savory (Satureja Hortensis L)mentioning
confidence: 99%
“…Evaluating the savory extract effect on the shelf-life of fresh chicken meat at refrigeration temperature showed that meat oxidation and its microbial load significantly decreased [175]. In another study where Satureja hortensis L. EO was utilized to reduce the survival of S. typhimorium in minced poultry meat during refrigerated storage, it was reported that summer savory EO significantly decreased Salmonella count compared to the control group [176]. Applying Satureja montana L. EO as antioxidants in precooked pork chops during chilled storage showed to be effective in oxidation stability and warmed-over flavor formation [177].…”
Section: Savory (Satureja Hortensis L)mentioning
confidence: 99%
“…Savoury plants (Satureja montana L.) are associated with compounds possessing antimicrobial properties: carvacrol, terpinen-4-ol, thymol, and linalool [68][69][70]. To reduce the concentration of S. montana compounds (due to the very intense flavour, it is not possible to include high concentrations in main food formulations) in ready-to-cook minced pork meat products, combinations of S. montana and sourdough LAB possessing antimicrobial properties were tested.…”
Section: Sourdough Lab-plant-based Bioproducts For Increasing the Fun...mentioning
confidence: 99%
“…Satureja montana L. antimicrobial properties are associated with carvacrol, terpinen-4-ol, thymol, and linalool (Dorman and Deans, 2000; Azimi et al, 2018; Pateiro et al, 2018). As combinations of antimicrobial compounds might promote increased effectiveness of the antimicrobial products and allow reduction of the dose of each compound needed, another experiment was performed by using the Satureja montana L. and antimicrobial properties having LAB compositions to improve meat products safety and quality.…”
Section: Lacto-fermented Satureja Montana L For Improving Value Of Rmentioning
confidence: 99%